2017
DOI: 10.1002/mp.12475
|View full text |Cite
|
Sign up to set email alerts
|

Assessing lung function using contrast‐enhanced dual‐energy computed tomography for potential applications in radiation therapy

Abstract: The extraction of iodine concentration maps from a contrast-enhanced DECT scan is achieved to compute the differential function for each lung subvolume and good agreement is found in respect to SPECT/CT. One promising avenue in radiation therapy is to include such functional information during treatment planning dose optimization to spare functional lung tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…The change in iodine concentration appeared to be a promising tool for predicting the tumor response to treatment for a variety of cancers . Iodine concentration mapping has also been proposed for determining the perfused blood volume, as a surrogate to pulmonary function, to guide treatment plan optimization and reduce pulmonary toxicities . An understanding of the accuracy of iodine quantitation with DECT is required before this application can be developed further for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…The change in iodine concentration appeared to be a promising tool for predicting the tumor response to treatment for a variety of cancers . Iodine concentration mapping has also been proposed for determining the perfused blood volume, as a surrogate to pulmonary function, to guide treatment plan optimization and reduce pulmonary toxicities . An understanding of the accuracy of iodine quantitation with DECT is required before this application can be developed further for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine maps derived by DE-CT may complement RECIST's twodimensional limitation by identifying cases where tumor viability has indeed decreased despite no change in tumor size 12 . Furthermore, they may also prove useful for riskstratifying radiotherapy patients prior to radiation 15 .…”
Section: Ct Approachesmentioning
confidence: 99%
“…In addition, dual-energy CT (DECT) provides images presenting the lung perfusion at a specific time point. By extraction and quantification of the iodine concentration, DECT provides the ratio of lobar perfusion of the lung, which allows accurate prediction of postoperative lung function [46,53]. Choe et al reported that a modified method incorporating postoperative lung volume change using DECT can be considered a comparable method for predicting postoperative lung function [54].…”
Section: Prediction Of Postoperative Lung Function or Postoperative Mmentioning
confidence: 99%